2003
DOI: 10.1029/2002je001886
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of melting process of the permafrost on Mars: Its implication for surface features

Abstract: [1] For supplying massive liquid water to the outflow channels, igneous melting of the permafrost layer could have played a significant role. We numerically simulate the melting process of the permafrost layer induced by magmatic intrusion. The point of our simulation is incorporation of thermal convection in porous media, which has not been modeled well in previous studies of the melting of the permafrost. Our results show that convection in the melted zone causes drastic change in heat transfer, which result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 22 publications
(37 reference statements)
0
20
0
Order By: Relevance
“…Its average specific heat over the 273 to 210 K temperature range that spans the cryosphere is ∼1900 J kg −1 K −1 , with the average temperature rise to reach the melting point being ∼31.5 K. Thus, for each meter along strike, to warm and melt all of the cryosphere ice in a typical 2 km wide part of the graben requires ∼3.0 × 10 14 J, only one tenth of the amount of heat available from the cooling dike. This implies that even allowing for the fact that the transfer of heat from the cooling dike to the more distal parts of the ice must have been relatively inefficient, despite the assistance of a hydrothermal convection system [ Gulick , 1998; Ogawa et al , 2003], we see no problem with justifying the proposal in section 3 that late stage graben floor subsidence amounts of up to 150 m were caused by this mechanism.…”
Section: Postflood Subsidence Of the Graben Floormentioning
confidence: 96%
See 1 more Smart Citation
“…Its average specific heat over the 273 to 210 K temperature range that spans the cryosphere is ∼1900 J kg −1 K −1 , with the average temperature rise to reach the melting point being ∼31.5 K. Thus, for each meter along strike, to warm and melt all of the cryosphere ice in a typical 2 km wide part of the graben requires ∼3.0 × 10 14 J, only one tenth of the amount of heat available from the cooling dike. This implies that even allowing for the fact that the transfer of heat from the cooling dike to the more distal parts of the ice must have been relatively inefficient, despite the assistance of a hydrothermal convection system [ Gulick , 1998; Ogawa et al , 2003], we see no problem with justifying the proposal in section 3 that late stage graben floor subsidence amounts of up to 150 m were caused by this mechanism.…”
Section: Postflood Subsidence Of the Graben Floormentioning
confidence: 96%
“…We calculate the total amount of sensible heat released by a dike 250 m thick cooling from an initial temperature of 1450 K (we assume that the dike was mafic) to some equilibrium temperature which is also taken to be the temperature of both the water and the rock components after cryosphere ice melting has occurred in the remaining 1750 m width of a zone 2 km wide. This zone is heated by a mixture of convection [ Ogawa et al , 2003] in the water component (assumed to be 10% of the volume on the basis of the Hanna and Phillips [2003, 2005b] models) and conduction through the rock component (the remaining 90% of the volume). This calculation is approximate because it neglects any latent heat of crystallization released by the magma and assumes that all of the available heat is confined to a zone with the width of the graben floor, whereas some of this heat may well be convected beyond this zone.…”
Section: Interpretation Of Morphologymentioning
confidence: 99%
“…Such an eruptive flow event would catastrophically release subsurface water causing collapse and disruption of the overlying surface. This would lead to outflow channels and chaotic terrains (Ogawa et al, 2003;El Maarry et al, 2012) that were not observed in the investigated area.…”
Section: Groundwater Sappingmentioning
confidence: 99%
“…Geothermal melting within permafrost produces a substantial amount of water close to the surface, which may erupt out of the ground (Ogawa et al, 2003). Such an eruptive flow event would catastrophically release subsurface water causing collapse and disruption of the overlying surface.…”
Section: Groundwater Sappingmentioning
confidence: 99%
“…While the triggers of these overland flows is debated, the main theories include: (1) melting of subsurface ice by near-surface magmatism (Chapman & Tanaka, 2002;Leask et al, 2006;Meresse et al, 2008;Ogawa, 2003;Rodriguez et al, 2005;Sharp, 1973), (2) release of subsurface water from a pressurized aquifer (Andrews-Hanna & Phillips, 2007;Carr, 1979;Clifford, 1993;Harrison & Grimm, 2009), (3) dewatering of subsurface gas-hydrates or evaporite minerals (Max & Clifford, 2001;Montgomery & Gillespie, 2005), (4) and melting of near-surface buried ice sheets (Roda et al, 2014;Zegers et al, 2010). Chaos terrain-floored craters are common in these dewatering regions, and form due to the release of subsurface groundwater, resulting in the fracturing and subsidence of overlying rock (Rodriguez et al, 2005).…”
Section: Comparison Of Proposed Calderas To Known Calderas On Mars Anmentioning
confidence: 99%